2019
DOI: 10.1111/jam.14220
|View full text |Cite
|
Sign up to set email alerts
|

Effects of potassium‐solubulizing and photosynthetic bacteria on tolerance to salt stress in maize

Abstract: Aims The purpose of this study was to determine the positive effects of potassium‐solubilizing bacteria and photosynthetic bacteria on the salt tolerance of maize. Methods and Results We selected the maize inbred lines USTB‐265 (salt‐sensitive), USTB‐109 (moderately salt‐tolerant) and USTB‐297 (salt‐tolerant) to investigate their growth characteristics, enzyme activity and gene expression in response to inoculation with photosynthetic bacteria and potassium‐solubilizing bacteria under salt‐stress conditions. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The biological process of release of K from minerals involves the activity of microorganisms. In the recent years, reports have been published on the utilization of silicate mineral weathering bacteria for crop improvement [1,[6][7][8][9][10][11]. Initially, only species of Bacillus were reported to weather silicate mineral.…”
Section: Introductionmentioning
confidence: 99%
“…The biological process of release of K from minerals involves the activity of microorganisms. In the recent years, reports have been published on the utilization of silicate mineral weathering bacteria for crop improvement [1,[6][7][8][9][10][11]. Initially, only species of Bacillus were reported to weather silicate mineral.…”
Section: Introductionmentioning
confidence: 99%
“…These results all indicate that the improvement in maize physiologies due to these inoculated strains played an important role in alleviating damage to maize due to salt stress. Feng et al ( 34 ) found that the activities of superoxide dismutase, catalase, and ascorbate in maize increased after inoculation with photosynthetic bacteria and potassium-enhancing bacteria, which effectively improved the salt tolerance of maize. Li et al ( 35 ) reported that a novel PGPR strain, Kocuria rhizophila , mitigated the deleterious effects of salinity on maize growth and development by regulating plant hormones and nutrient acquisition, thereby maintaining ionic homeostasis and improving photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers stated that growth and yield traits of corn could be significantly improved by the addition of PSB and KSB, compared with the control (Yadav et al, 2018;Feng et al, 2019). Beneficial bacteria can avoid ion toxicity by regulating various physiological processes of plants in saline soil (Ilangumaran and Smith, 2017), with improved water-salt balance, and ion balance under saline conditions by regulating the transpiration rate, carbohydrate transport, and K + transporter activity of corn (Marulanda et al, 2010;Rojas-Tapias et al, 2012).…”
Section: Discussionmentioning
confidence: 99%